Altered Spontaneous Brain Activity Related to Neurologic and Sleep Dysfunction in Children With Obstructive Sleep Apnea Syndrome - Bai, Jie; Wen, Hongwei; Tai, Jun; Peng, Yun; Li, Hongbin; Mei, Lin; Ji, Tingting; Li, Xiaodan; Li, Yanhua; Ni, Xin; Liu, Yue (Frontiers in Neuroscience, 2021)
Childhood Obstructive sleep apnea (OSA) is a common chronic sleep-related breathing disorder in children, which leads to growth retardation, neurocognitive impairments and serious complications. Considering the previous studies about brain structural abnormalities in OSA, in the present study we aimed to explore the altered spontaneous brain activity among OSA patients, using amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF) and regional homogeneity (ReHo) methods based on resting-state functional magnetic resonance imaging (MRI).Thirty-one untreated OSA children and thirty-three age-and gender-matched healthy children (HC) were included in this study. Compared with controls, OSA group showed significant lower ALFF in the right lingual gyrus, decreased fALFF in the left middle frontal gyrus (MFG) , whereas increased fALFF in the left precuneus. Decreased ReHo were found in the left inferior frontal gyrus (orbital part) and left middle frontal gyrus. Notably, the mean fALFF value of left MFG was not only significantly related to multiple sleep parameters, but also demonstrated the best performance in ROC curve analysis. These findings revealed OSA children associated with dysfunctions in the default mode network, the frontal lobe and the lingual gyrus, which may implicate the underlying neurophysiological mechanisms of intrinsic brain activity. The correlation between the altered spontaneous neuronal activity and the clinical index provides early useful diagnostic biomarkers for OSA children as well.